Медицинские проблемы безопасности жизнедеятельности - Нетудыхатка, О.Ю. (Актуальні проблеми транспортної медицини, 2005)
In the work presented they briefly describe the
main problems having an effect on a human being's vital functions and validate some paths and methods of diminishing negative conditions adversely affecting at a human being and decreasing his fitness to work, causing the diseases onset and leading to various dangerous situations.